Cultural Matters in an English Course: Beyond Local Versus Target Language Cultural Matters - Nuur Insan Tangkelangi; Kalvin Sandabunga; Edi Wahyono (Universitas Cokroaminoto Palopo, 2022)
This study aims at finding out whether materials in an English course embrace local and/or target language culture. To investigate this issue, learning materials of the course were analysed. This learning materials were seen in the syllabus, lesson plan, and the learning sources used in the course. The results of the analysis show that the course embed both local and target language cultures. Interestingly, the materials also embed global cultures which means the contexts discussed are not merely limited to local and/or target language contexts but also contexts in various countries. Both local and target language cultures can be found in the examples used in grammar materials. Meanwhile, global contexts can be seen in language skills contents. Beside of discussing the example uses of local and target language cultures, this article also discusses several debated points of the use of these cultures. Then, at the end of this article a reflective conclusion is presented.